Adjudicating trade and investment disputes : convergence or divergence? / edited by Szilárd Gáspár-Szilágyi, Daniel Behn, Malcolm Langford. - Gáspár-Szilágyi, Szilárd, 1987-; Behn, Daniel, 1974-; Langford, Malcolm (Studies on international courts and tribunals., 2020)
Recent trends suggest that international economic law may be witnessing a renaissance of convergence - both parallel and intersectional. The adjudicative process also reveals signs of convergence. These diverse claims of convergence are of legal, empirical and normative interest. Yet, convergence discourse also warrants scepticism. This volume contributes to both the general debate on the fragmentation of international law and the narrower discourse concerning the interplay between international trade and investment, focusing on dispute settlement. It moves beyond broad observations or singular case studies to provide an informed and wide-reaching assessment by investigating multiple standards, processes, mechanisms and behaviours. Methodologically, a normative stance is largely eschewed in favour of a range of 'doctrinal,' quantitative and qualitative methods that are used to address the research questions. Furthermore, in determining the extent of convergence or divergence, it is important to recognize that there is no bright line or clear yardstick for determining its nature or degree.